Impedance spectroscopy-based cell/particle position detection in microfluidic systems. Issue 7 (7th March 2017) - Wang, H.; Sobahi, N.; Han, A.
Abstract : A high-throughput and low-cost impedance spectroscopy-based microfluidic platform capable of detecting/discriminating the transverse positions of cells/particles flowing within a microfluidic channel. Abstract : An impedance spectroscopy-based cell/particle position detection method in microfluidic systems is presented. A single pair of non-parallel surface microelectrodes was utilized to detect the transverse positions of particles/cells flowing in a microchannel without the need for a multi-electrode multi-channel impedance detection. This method can be a simple solution for high-throughput and low-cost position detection in microfluidic sorting and separation applications.